The Psychological Impact of Social Expectations on Women’s Personal Choices - Kamyab, Fatemeh; Hoseinzadeh, Aliasghar (Psychology of Woman Journal, 2023)
Objective: This study aims to explore the psychological impact of social expectations on women’s personal choices. Methods and Materials: The study employs a qualitative research design, utilizing semi-structured interviews to gather in-depth insights from 30 diverse women. Participants were selected through purposive sampling to represent various age groups, socio-economic statuses, educational backgrounds, and cultural contexts. Data collection continued until theoretical saturation was achieved. The interviews were transcribed and analyzed using NVivo software, following a systematic coding process to identify key themes and subthemes related to the research questions. Findings: Three major themes emerged from the analysis: Identity and Self-Perception, Interpersonal Relationships, and Mental Health and Well-Being. Participants reported significant pressure from societal beauty standards, gender roles, and traditional social expectations, impacting their self-esteem, career choices, and social roles. Family dynamics, romantic relationships, and peer influences further complicated their decision-making processes. The pressure to meet societal standards also led to considerable stress, anxiety, and challenges in emotional regulation. Women employed various coping strategies, including resilience, support systems, and self-care practices, to manage these pressures. Conclusion: The findings underscore the profound influence of social expectations on women’s psychological well-being and personal choices. These expectations create significant internal and external conflicts, affecting women’s identities, relationships, and mental health. The study highlights the need for supportive interventions and societal changes to promote gender equity and empower women to make autonomous decisions. Future research should expand on these findings with larger, more diverse samples and explore the intersectionality of various social identities.